Carbon dioxide hydrate formation with SDS: Further insights into mechanism of gas hydrate growth in the presence of surfactant. (1st January 2019) - Molokitina, Nadezhda S.; Nesterov, Anatoliy N.; Podenko, Lev S.; Reshetnikov, Aleksey M.
Highlights: CO2 hydrate growth with/without SDS was studied. CO2 hydrate film grows on the water side of the gas-water interface. Location of the CO2 hydrate film growth with SDS is dependent on a driving force. SDS effect on the CO2 hydrate growth is absent at large driving forces. CO2 hydrate grows with SDS by a capillary-driven mechanism at small driving forces. Abstract: The capillary-driven mechanism of gas hydrate growth after their nucleation in the presence of surfactants under quiescent conditions is well-known for methane and other hydrocarbons gases but has not been observed previously for carbon dioxide (CO2 ). We have investigated the CO2 hydrate growth with sodium dodecyl sulfate (SDS) under different mass-transfer driving forces Δ x, that is the difference between the equilibrium solubility of gas in liquid and the amount of gas dissolved in the liquid (mole concentration) in equilibrium with the hydrate. The kinetics data on gas consumption and the results of microscopic investigation of the hydrate film growth at the gas-liquid interface as well as hydrate growth in the bulk liquid and in the gas phase upward from the gas-liquid interface (the capillary-driven growth) are presented. An effect of the driving force on the CO2 hydrate formation was examined. It was found that under the large driving force (Δ x ≥ 5.0 × 10 −3 ), SDS additives in the concentration of 100, 1000 and 5000 ppm had no effect on the mechanism and kinetics of the CO2 hydrate growth. For the small driving force (Δ x ≤ 1.0 × 10 −3 ) and the SDS concentration of 1000 ppm the capillary-driven growth of CO2 hydrates was observed for the first time. The amount of the water converted into the hydrate during the capillary-driven growth of CO2 hydrates without stirring in the presence of 1000 ppm SDS achieved about 90%.